Catalisadores de ródio(I) para hidroformilação e hidrogenação de olefinas ancoradas eletrostaticamente em resinas de troca iônica - Glenda Aparecida de Carvalho (2009)
In this work, rhodium(I) catalysts was anchored on commercial anion-exchange resins by the sodium 3-sulfonatophenyldiphenylphosphine (TPPMS). The catalysts were employed for the hydroformylation or the hydroformylation/acetalyzation of α-olefins, as well as the hydrogenation of unsaturated steroids. The commercial anion-exchange resins used were Amberlite IRA-96 (weakly basic) protonated by HCl or IRA-900 (strongly basic) exchanged with chloride. The anions were exchanged with TPPMS, and put in contact with a toluene solution of bis[(1,5-cyclooctadiene)(µ-methoxide)rhodium(I)], [Rh(cod)(µ-OMe)]2. The resulting catalysts were characterized by Kevex X-ray analyses (rhodium and phosphor), infrared spectroscopy and scanning electronic microscopy. The catalyst IRA96/TPPMS/Rh was employed for the hydroformylation of allylbenzenes obtained from natural sources eugenol and estragole. The reaction was carried in toluene at 70-90 oC, under 40-60 bar of hydrogen and carbon monoxide (1:2 to 2:1) to give aldehydes with a formyl group in the γ (main product) or β position with respect to the aromatic ring, along with the isomeric olefin and the hydrogenated product. The catalyst showed activity and selectivity comparable with the homogeneous systems under similar conditions and could be recycled, but with loss in activity. When alcohols (methanol, ethanol) were employed as solvents, the aldehydes primarily formed were converted “in situ” to the corresponding acetals in moderated yields. The catalyst IRA900/TPPMS/Rh was employed on the hydroformylation of eugenol, estragole, limonene, as well as the vinylbenzenes styrene and methylstyrene. The reactions were carried in toluene at 50-70 oC, under 40-60 bar of hydrogen and carbon monoxide (1:2 to 2:1) to give aldehydes with the formyl group in the γ (main product) or β position with respect to the aromatic ring for allylbenzenes, in the α (main product) or beta-position for vinylbenzenes, and in the beta position with respect to the cyclohexene ring for limonene. The catalyst showed activity and selectivity comparable with the homogeneous systems under similar conditions and were used in three batches (two recycles), with complete conversion of the substrate in 24 h. When alcohols (methanol, ethanol) were employed as solvents, the aldehydes primarily formed were converted “in situ” to the corresponding acetals in good yields. The catalyst was used in three batches (two recycles) with complete conversion of the substrate after 24h. For the homogeneous catalysts, the aldehydes were not converted efficiently to acetals. Both catalysts IRA900/TPPMS/Rh and IRA96/TPPMS/Rh were employed on the selective hydrogenation of the steroids 4-androstene-3,17-dione and 3β-acetoxypregna-5,16-dien-20-one. These immobilized catalysts could selectively reduce C-C double bonds leading to the preferential formation of the α -diastereoisomer, as in the homogeneous systems. Also in this case the catalyst was used in three batches (two recycles) with complete conversion of the substrate after 24h.